Rational design of metallic nanowire-based plasmonic architectures for efficient inverted polymer solar cells. (December 2015) - Yang, Yuzhao; Qing, Jian; Ou, Jiemei; Lin, Xiaofeng; Yuan, Zhongke; Yu, Dingshan; Zhou, Xiang; Chen, Xudong
Graphical abstract: Highlights: The location effects of nanowires on the performance of PSCs were studied. Three kinds of plasmonic structures were designed to investigate location effects. Steady state PL and TRPL were used to study the effects of pre-designed structures. The optimized pre-designed plasmonic inverted PSC showed the PCE up to 4.05%. Abstract: Plasmonics can improve the performance of polymer solar cells (PSCs) by localizing and concentrating light, and the location of the plasmonic metallic nanostructure in devices plays an important role in how to design high-performance plasmonic solar cells. Here, by varying the location of silver nanowires (Ag NWs) within the device architecture (at the interface between indium–tin–oxide and cathode buffer layer, cathode buffer layer and active layer, active layer and anode buffer layer, respectively), a systematic study on plasmonic effect on the properties of photovoltaic material was presented. The density of photogenerated excitons, the electron delocalization and the effective conjugation length of the photovoltaic material in our pre-designed plasmonic structures were increased, and the enhancements of plasmonic effects were effective in a broad spectral range. When the pre-designed plasmonic structures were incorporated into the inverted PSCs, short circuit current density ( J sc ) for all the investigated structures showed increase. The optimal inverted device performance was achieved when the Ag NWs were located at the interface of indium–tin–oxide and cathode buffer layer. The power conversion efficiency of the optimized plasmonic inverted device reached 4.05% under AM1.5 illumination (100 mW/cm 2 ), which was due to the enhancement of J sc without reducing the open-circuit voltage and FF of the plasmonic inverted PSCs by introducing Ag NWs.